Molded body, downhole tool member, and downhole tool
By adding a composition of specific cyclic ester and inorganic filler to the glycolic acid polymer, the problem of insufficient decomposition speed of molded bodies in downhole tool components is solved, and the thickness reduction speed is improved while maintaining tensile strength and The effect of decomposition speed.
Patent Information
- Application Number
- CN202380038505.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-03-28
- Publication Date
- 2024-12-13
AI Technical Summary
In the downhole tool member, the decomposition speed of the glycolic acid polymer molded body with a thickness of more than 5 mm is insufficient, and it is difficult to increase the thickness reduction speed while maintaining the tensile strength.
By adding specific cyclic esters and inorganic fillers to the glycolic acid polymer, the content of cyclic esters is 10% or more than 22%, the content of inorganic fillers is 0.1% or more than 15%, and it is free aluminum nitride The molded body formed by the composition composed of silicon nitride increases the thickness reduction rate after decreasing from an initial thickness of 5 mm or more, and suppresses the decrease in tensile strength at 49°C.
While maintaining tensile strength, the thickness reduction speed after reducing the initial thickness by more than 5 mm is achieved, the complete decomposition time of the molded body is shortened, and the thickness reduction speed of the molded body is enhanced.
Smart Images

Figure BDA0005118780400000141 
Figure BDA0005118780400000191 
Figure BDA0005118780400000201
Abstract
Description
Technical Field
[0001] The present invention relates to a molded body composed of a composition containing a glycolic acid polymer, a downhole tool component composed of the molded body, and a downhole tool comprising the downhole tool component. Background Art
[0002] Glycolic acid polymer is a degradable resin material with high strength, hydrolysis and decomposition. Glycolic acid polymer is used as bone fixation material and medical materials such as sutures by taking advantage of its characteristics. In recent years, its use has been expanding as a component of downhole tools for recovering oil and gas resources. Due to the requirement for higher decomposition speed depending on the application, various research and development are being conducted to improve the decomposition speed of glycolic acid polymer.
[0003] For example, Patent Document 1 discloses that a decomposable polymer material forming a decomposable sealing member for a downhole tool may contain glycolide, lactide, phthalic anhydride or the like as a decomposition accelerator.
[0004] Furthermore, Patent Document 2 discloses that a molded article having an effective thickness of 1 mm or more is formed from an aliphatic polyester resin composition containing a specific amount of carboxylic anhydride, and that the molded article has excellent decomposability even at a temperature lower than 66°C.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-143333
[0008] Patent Document 2: Japanese Patent Application Publication No. 2015-172106 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] When a molded article containing glycolic acid polymer is used in a member of a downhole tool, the decomposition rate of the molded article is required to be further increased. In particular, for a molded article having a thickness of more than 5 mm, the thickness reduction rate after the initial thickness is reduced by more than 5 mm is required to be increased while maintaining the tensile strength.
[0011] An object of one embodiment of the present invention is to achieve a molded body having an increased thickness reduction rate after the thickness is reduced by 5 mm or more from the initial thickness while maintaining the tensile strength.
[0012] Technical Solution
[0013] The present inventors have conducted intensive studies and found that the thickness reduction rate of a molded article after the initial thickness is reduced by 5 mm or more is increased by including a specific cyclic ester and a specific inorganic filler in a composition containing a glycolic acid polymer. Furthermore, the inventors found that the decrease in the tensile strength of the molded article at 49° C. is suppressed, thereby completing the present invention.
[0014] A molded body according to one embodiment of the present invention is formed from a composition comprising a glycolic acid polymer, a cyclic ester, and an inorganic filler, wherein the content of the cyclic ester in the composition is 10% by mass or more and 22% by mass or less, the content of the inorganic filler is 0.1% by mass or more and 15% by mass or less, the inorganic filler is at least one inorganic filler selected from the group consisting of aluminum nitride and silicon nitride, and the thickness or diameter of the molded body is greater than 5 mm.
[0015] Beneficial Effects
[0016] According to one aspect of the present invention, it is possible to provide a molded body having an improved thickness reduction rate after the thickness is reduced by 5 mm or more from the initial thickness while maintaining the tensile strength. DETAILED DESCRIPTION
[0017] 〔Molding body〕
[0018] A molded article according to one embodiment of the present invention is formed from a composition containing a glycolic acid polymer, a cyclic ester, and an inorganic filler.
[0019] (Glycolic Acid Polymer)
[0020] In this specification, the glycolic acid polymer refers to a polymer containing repeating units derived from glycolic acid (-(-O-CH2-CO-)-). The glycolic acid polymer may be a homopolymer of glycolic acid (polyglycolic acid (PGA)). In addition, the glycolic acid polymer may also be a copolymer containing repeating units derived from glycolic acid and repeating units derived from other monomers.
[0021] Hereinafter, a copolymer including a repeating unit derived from glycolic acid and a repeating unit derived from another monomer (hereinafter referred to as a "glycolic acid copolymer") will be described.
[0022] (Glycolic Acid Copolymer)
[0023] From the viewpoint of improving the decomposition rate, the glycolic acid copolymer may be a copolymer in which two or more linear polymer chains A composed of repeating units derived from glycolic acid are chemically bonded to polymer chains B different from the polymer chains A. The polymer chains A and B are described below.
[0024] In the glycolic acid copolymer, polymer chain A and polymer chain B may be chemically bonded to two or more polymer chains, and the bonding position of polymer chain A in polymer chain B is not particularly limited. For example, the copolymer may be a triblock copolymer ("ABA type block copolymer", wherein A is the polymer chain A and B is the polymer chain B) formed by chemically bonding the two ends of the main chain of polymer chain A and polymer chain B, or a graft copolymer formed by graft bonding two or more polymer chain A blocks to polymer chain B.
[0025] The copolymer is preferably an ABA type block copolymer (wherein A is the polymer chain A and B is the polymer chain B) because the effect of improving the thickness reduction rate during decomposition when the glycolic acid copolymer is formed into a molded product is more excellent.
[0026] In the glycolic acid copolymer, the polymer chain A and the polymer chain B are preferably bonded via an ester bond. This has the effect of easily increasing the thickness reduction rate during decomposition when the glycolic acid copolymer composition is formed into a molded article.
[0027] In particular, when polymer chain B is a unit having higher hydrophilicity or flexibility than polymer chain A, it is particularly preferred that polymer chain A and polymer chain B are bonded via an ester bond. Specifically, when polymer chain B is a unit having higher hydrophilicity or flexibility than polymer chain A, water easily penetrates into the vicinity of polymer chain B compared to the vicinity of polymer chain A, and the ester bond between polymer chain A and polymer chain B is more easily hydrolyzed than the ester bond in polymer chain A. That is, the ester bond between polymer chain A and polymer chain B is hydrolyzed, and the glycolic acid copolymer is cut between polymer chain A and polymer chain B, thereby significantly reducing its molecular weight and facilitating the thickness reduction rate.
[0028] Hereinafter, the polymer chain A and the polymer chain B constituting the glycolic acid copolymer will be described. (Polymer chain A)
[0029] Examples of polymer chain A include linear polymer chains composed of glycolic acid units. The number of glycolic acid units constituting one block of polymer chain A in the glycolic acid copolymer is not particularly limited and can be appropriately determined within the range in which the glycolic acid copolymer can exhibit decomposability derived from polymer chain A.
[0030] (Polymer chain B)
[0031] The polymer chain B is a polymer chain different from the polymer chain A. For example, the polymer chain B may be a polymer chain derived from a polymer compound having a glass transition temperature (Tg) of less than 45° C. Alternatively, the polymer chain B may be a polymer chain derived from a polymer compound having a weight average molecular weight of 1,500 to 250,000.
[0032] From the viewpoint of making the glass transition temperature of the glycolic acid copolymer lower than the glass transition temperature of the polymer composed only of the polymer chain A, the glass transition temperature of the polymer compound serving as the source of the polymer chain B (hereinafter, "polymer compound B") is preferably 45° C. or less, and more preferably 0° C. or less. The glass transition temperature of the polymer compound serving as the source of the polymer chain B can be measured by differential scanning calorimetry (DSC).
[0033] From the viewpoint of further improving the thickness reduction rate during the decomposition of the molded body, the weight average molecular weight of the polymer compound B is preferably 2500 or more, more preferably 3000 or more, and more preferably 7500 or more. In addition, from the viewpoint of improving the strength of the molded body, the weight average molecular weight of the polymer compound B is preferably 50000 or less, more preferably 20000 or less. The weight average molecular weight of the polymer compound B is 50000 or less, which is also advantageous from the viewpoint of controlling the solubility and copolymerization reactivity in glycolide during the polymerization of the glycolic acid copolymer. The weight average molecular weight of the polymer compound B can be measured using a gel permeation chromatography (GPC) device.
[0034] The polymer compound B is not particularly limited as long as it is a polymer compound other than polyglycolic acid. In order to function as a polymerization initiator, the polymer compound other than polyglycolic acid has functional groups at two or more ends that can chemically bond to the glycolic acid units constituting the polymer chain A and has a weight average molecular weight and / or glass transition temperature within the above-mentioned specific range.
[0035] As such a polymer compound B, for example, polyols having the above-mentioned specific weight average molecular weight and glass transition temperature can be cited. Examples of polyols include polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, polycaprolactone, polydioxanone, polydimethylsiloxane, polyethylene oxalate, etc. "Polyol" can be a homopolymer consisting of only one repeating unit, or a copolymer further comprising repeating units derived from other monomers.
[0036] From the viewpoint of imparting hydrophilicity to the glycolic acid copolymer, the polymer compound B is preferably a hydrophilic polyol polymer having a terminal hydroxyl group. Examples of the hydrophilic polyol polymer having a terminal hydroxyl group include polyethylene glycol, polypropylene glycol, polyglycerol, polyvinyl alcohol, and the like.
[0037] In one embodiment of the present invention, the polymer compound B may be a hydrophilic polyol having a terminal hydroxyl group and a weight average molecular weight of 3000 to 50000. When the polymer compound B is a hydrophilic polyol having a terminal hydroxyl group and a weight average molecular weight of 3000 to 50000, the hydrophilicity of the polymer chain B is manifested in the glycolic acid copolymer, and the affinity with water is improved during decomposition, resulting in an effect of further improving the thickness reduction rate of the molded body during decomposition.
[0038] In another embodiment of the present invention, the polymer compound B may be polyethylene glycol or polypropylene glycol having a weight average molecular weight of 3000 to 50000. Polyethylene glycol and polypropylene glycol have particularly low glass transition temperatures and particularly high hydrophilicity. Therefore, by using polyethylene glycol or polypropylene glycol as the hydrophilic polyol having terminal hydroxyl groups, the glycolic acid copolymer can be given flexibility and hydrophilicity.
[0039] In another embodiment of the present invention, polymer compound B may be polyethylene glycol having a weight average molecular weight of 7500 to 50000. Polymer compound B may be polyethylene glycol having a weight average molecular weight of 7500 to 50000, which further increases the thickness reduction rate of the molded article during decomposition.
[0040] The polymer compound B may be a homopolymer composed of repeating units derived from a single monomer, or may be a copolymer further including repeating units derived from other monomers.
[0041] As other monomers, for example, cyclic monomers such as vinyl oxalate (1,4-dioxane-2,3-dione), lactides, lactones (such as β-propiolactone, β-butyrolactone, β-pivalolactone, γ-butyrolactone, δ-valerolactone, β-methyl-δ-valerolactone, ε-caprolactone, etc.), carbonates (such as trimethylene carbonate, etc.), ethers (such as 1,3-dioxane, etc.), aliphatic ethers (such as p-dioxanone, etc.), and amides (ε-caprolactam, etc.); hydroxycarboxylic acids such as lactic acid, 3-hydroxypropionic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, and 6-hydroxyhexanoic acid, or their alkyl esters; substantially equimolar mixtures of aliphatic diols such as ethylene glycol, propylene glycol, tetramethylene ether glycol, and 1,4-butanediol and aliphatic dicarboxylic acids such as succinic acid and adipic acid, or their alkyl esters; or two or more thereof can be listed.
[0042] From the viewpoint of adjusting the physical properties of polymer compound B, repeating units derived from other monomers can be used. For example, by adopting other repeating units, the affinity of polymer compound B for water can be adjusted. The content of other repeating units in polymer compound B can be appropriately determined within the range of fully obtaining the desired effect achieved by polymer chain B. For example, the content of repeating units derived from other monomers in polymer compound B can be 50% by mass or less, preferably 30% by mass or less, and more preferably 10% by mass or less. Polymer compound B can be linear or a graft copolymer formed by graft bonding of other polymer compounds.
[0043] The polymer chain B may have an ester bond in the molecule. Since the polymer chain B has an ester bond in the molecule, cleavage by hydrolysis of the ester bond also occurs in the polymer chain B, the thickness reduction rate is more likely to be increased.
[0044] From the viewpoint of fully expressing the hydrophilicity of the polymer chain B in the glycolic acid copolymer and improving the thickness reduction rate of the molded article during decomposition, the amount of the polymer chain B in the glycolic acid copolymer is preferably 0.5 or more, more preferably 1.5 or more, based on the mass ratio, relative to the total amount of the polymer chain A (100). Furthermore, from the viewpoint of maintaining the strength of the glycolic acid copolymer, the amount of the polymer chain B in the glycolic acid copolymer is preferably 30 or less, more preferably 20 or less, based on the mass ratio, relative to the total amount of the polymer chain A (100).
[0045] The glycolic acid polymer can be produced by a known method. For example, the glycolic acid copolymer can be appropriately produced by the following method: using a polymer compound B that is the source of the polymer chain B as a polymerization initiator, in the presence of a small amount of catalyst and under conditions where the solvent is substantially absent (i.e., bulk polymerization conditions), glycolide, which is a dimer of glycolic acid, is subjected to ring-opening polymerization. The reaction temperature of the ring-opening polymerization can be appropriately determined within a range in which the ring-opening polymerization of glycolide is appropriately carried out, for example, 140° C. Examples of the above-mentioned catalyst include cationic catalysts such as organic carboxylic acid tin, tin halide, and antimony halide. Commercially available products can also be used for glycolic acid polymers.
[0046] (Cyclic esters)
[0047] The cyclic ester contained in the above composition can be, for example, at least one cyclic ester selected from the group consisting of glycolide, lactide, ε-caprolactone, γ-valerolactone, δ-valerolactone, diglycolic anhydride and glutaric anhydride, preferably a cyclic ester selected from the group consisting of glycolide, lactide, ε-caprolactone, γ-valerolactone and δ-valerolactone. Among the above cyclic esters, glycolide is more preferred because of the chemical structure with the highest compatibility with PGA. Cyclic esters can be used alone or in combination of two or more. (Fedors' solubility parameter)
[0048] In the composition of the present embodiment, the absolute value of the difference between the solubility parameter of the cyclic ester Fedors and the solubility parameter of the glycolic acid polymer is 6 (J / cm 3 ) 1 / 2 Below, preferably 5.5 (J / cm 3 ) 1 / 2 Below, more preferably 5 (J / cm 3 ) 1 / 2 Hereinafter, the "Fedors solubility parameter" may be simply referred to as "SP value." When the absolute value of the difference between the SP value of the cyclic ester and the SP value of the glycolic acid polymer is within the above range, the composition has sufficient plasticity.
[0049] The SP value can be calculated, for example, by "SP Value Fundamentals / Application and Calculation Method" by Hideki Yamamoto (published by Information System Co., Ltd. (2005) pp. 66-67). More specifically, the SP value δ (cal / cm2) of the target compound (glycolic acid polymer or cyclic ester) is calculated according to the following formula (1): 3 ) 1 / 2 ).
[0050] δ=(ΣEcoh / ΣV) 1 / 2 ……(1)
[0051] In formula (1), ΣEcoh represents Ecoh (the cohesive energy density (cal / cm 3 ));ΣV represents V(the molar molecular volume (cm 3 )).
[0052] When the composition contains two or more cyclic esters, the absolute value of the difference between the SP value of at least one cyclic ester and the SP value of the glycolic acid polymer is 6 (J / cm 3 ) 1 / 2 the following.
[0053] The content of the cyclic ester in the above composition is 10% by mass or more relative to 100% by mass of the composition, preferably 12% by mass or more, more preferably 15% by mass or more. In addition, the content is 22% by mass or less, preferably 20% by mass or less, more preferably 18% by mass or less, and further preferably 17% by mass or less. When the content of the cyclic ester is within the above range, the glass transition temperature (Tg) of the composition can be fully reduced, and sufficient plasticity is imparted to the composition.
[0054] (Inorganic filler)
[0055] The inorganic filler contained in the above composition is at least one inorganic filler selected from the group consisting of aluminum nitride and silicon nitride. The above inorganic filler is a nitride that hydrolyzes when in contact with water to generate ammonia. The generated ammonia hydrolyzes the nearby glycolic acid polymer to form micropores. It is speculated that if micropores exist in the glycolic acid polymer composition, the diffusion of water is improved, thereby promoting decomposition. Among the above inorganic fillers, aluminum nitride that is easily hydrolyzed is preferred. The inorganic filler can be used alone or in combination of two or more.
[0056] The shape of the inorganic filler is not particularly limited, and inorganic fillers such as fibrous, whisker, plate (layer), powder or particle can be used. The inorganic filler is preferably in particle form. By making it into a particle form, the agglomeration of the inorganic filler can be suppressed. In addition, the specific surface area of the inorganic filler when in contact with the polymer matrix increases, which can increase the contact efficiency of the interface where the inorganic filler contacts the polymer matrix, so the decomposition rate is improved.
[0057] The content of the inorganic filler in the above composition is 0.1% by mass or more relative to 100% by mass of the composition, preferably 0.3% by mass or more, more preferably 0.5% by mass or more, and further preferably 1% by mass or more. In addition, the content is 15% by mass or less relative to 100% by mass of the composition, preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 3% by mass or less. When the content of the inorganic filler is within the above range, the water absorption of the molded body formed by the composition is increased by decomposition of the inorganic filler, and the thickness reduction rate of the molded body is further increased.
[0058] From the perspective of increasing the thickness reduction rate in the later stage of decomposition and increasing the tensile strength of the molded body, the content of the cyclic ester and the inorganic filler in the above-mentioned composition is more preferably 10 mass % or more and 15 mass % or less, and further preferably 12 mass % or more and 5 mass % or less, respectively, relative to 100 mass % of the composition.
[0059] (Weight average molecular weight of composition)
[0060] From the perspective of maintaining the strength of the molded body and the perspective of extrusion molding, the weight average molecular weight (Mw) of the composition is preferably 150,000 or more, more preferably 160,000 or more, and further preferably 170,000 or more. In addition, from the perspective of facilitating molding during extrusion molding or injection molding, the Mw of the composition is preferably 500,000 or less, more preferably 450,000 or less, and further preferably 400,000 or less.
[0061] The weight average molecular weight of the above composition can be measured, for example, by the method shown below: about 10 mg of the composition is dissolved by heating with 0.5 mL of DMSO at 150° C. and cooled to room temperature. The cooled solution is fixed to 10 mL with hexafluoroisopropanol (HFIP), and the weight average molecular weight of the composition is measured using a gel permeation chromatography (GPC) device. As a standard substance, polymethyl methacrylate (PMMA) is used. As a GPC device, shodexGPC-104 (detector: RI, chromatographic column: two HFIP-606M) can be listed. In addition, as a solvent, HFIP containing 5 mM CF3COONa can be used.
[0062] (Other ingredients)
[0063] The above composition may contain other components in addition to the glycolic acid polymer, the cyclic ester and the inorganic filler within a range not contradicting the purpose of the present invention.
[0064] Examples of other components include various additives such as plasticizers, heat stabilizers, light stabilizers, moisture proof agents, water repellents, hydrophobic agents, lubricants, hydrophilic agents, water absorbents, nucleating agents, pore-increasing agents, etc. In addition, the composition may also contain a polymerization initiator and a catalyst for producing a polymer.
[0065] In this specification, the decomposition promoter refers to an agent (compound) that promotes the hydrolysis reaction of the composition containing the glycolic acid polymer. Examples of the decomposition promoter include carboxylic anhydride and phosphorus compound. The decomposition promoter may be used alone or in combination of two or more.
[0066] There is no particular limitation on the carboxylic anhydride in the composition. From the viewpoint of heat resistance to withstand the temperature at which the composition is molded and the viewpoint of compatibility with the composition, a carboxylic anhydride having a ring structure is preferred, and more preferably hexanoic anhydride, caprylic anhydride, capric anhydride, lauric anhydride, myristic anhydride, palmitic anhydride, stearic anhydride, benzoic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, trimellitic anhydride, tetrahydrophthalic anhydride, butanetetracarboxylic anhydride, 3,3′,4,4 '-benzophenonetetracarboxylic dianhydride, diphenylsulfonetetracarboxylic dianhydride, biphenyltetracarboxylic dianhydride, ethylene glycol dianhydrotrimellitate, glycerol dianhydrotrimellitate monoacetate and benzene-1,2,4,5-tetracarboxylic anhydride (pyromellitic anhydride), particularly preferably phthalic anhydride, trimellitic anhydride, benzoic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, benzene-1,2,4,5-tetracarboxylic anhydride (pyromellitic anhydride).
[0067] The phosphorus compound in the composition is not particularly limited, but is preferably an organic phosphorus compound such as phosphate and phosphite, and more preferably an organic phosphorus compound having at least one structure selected from the group consisting of a long-chain alkyl group having 8 to 24 carbon atoms, an aromatic ring, and a pentaerythritol skeleton.
[0068] Examples of phosphoric acid esters having a long-chain alkyl group with 8 to 24 carbon atoms include mono- or di-stearyl acid phosphate or a mixture thereof, and di-2-ethylhexyl acid phosphate. Examples of phosphites having an aromatic ring include tris(nonylphenyl)phosphite. Examples of phosphites having a pentaerythritol skeleton structure include cycloneopentanylidene tetraylbis(2,6-di-tert-butyl-4-methylphenyl)phosphite, cycloneopentanylidene tetraylbis(2,4-di-tert-butylphenyl)phosphite, and cycloneopentanylidene tetraylbis(octadecyl)phosphite.
[0069] The content of the decomposition accelerator in the above-mentioned composition is preferably 1% by mass, more preferably 3% by mass or more relative to 100% by mass of the composition. In addition, relative to 100% by mass of the composition, the content is preferably 10% by mass or less, more preferably 7% by mass or less, and further preferably 5% by mass or less. If the content of the decomposition accelerator is within the above-mentioned range, the decomposition accelerator is not easy to ooze out from the composition, so the decomposition speed of the composition can be promoted, and the molding processing of the composition is made easy.
[0070] The above composition can be prepared by mixing a glycolic acid polymer, a cyclic ester and an inorganic filler. The cyclic ester can also be added when preparing the glycolic acid polymer. In addition, when the glycolic acid polymer is obtained by ring-opening polymerization of glycolide, the residual glycolide can also be used as the cyclic ester. That is, the composition can also be prepared by mixing a glycolic acid polymer composition containing glycolide and a glycolic acid polymer obtained by preparing a glycolic acid polymer, an inorganic filler and an arbitrary plasticizer.
[0071] A molded article according to one embodiment of the present invention is a polyglycolic acid molded article formed from the above composition, and the thickness or diameter of the molded article is greater than 5 mm.
[0072] When the molded body of one embodiment of the present invention is kept in water at 49°C, the rate of thickness reduction of the molded body after the initial thickness (the thickness of the molded body before being kept in water) is reduced by more than 5 mm is preferably 0.070 mm / hour or more, and more preferably 0.090 mm / hour or more. Hereinafter, "the molded body after the initial thickness is reduced by more than 5 mm when kept in water at 49°C" is sometimes expressed as "the molded body in the late stage of decomposition". When the rate of thickness reduction of the molded body in the late stage of decomposition is 0.070 mm / hour or more, the time required for complete decomposition of the molded body within the desired time can be shortened. Therefore, the thickness of the molded body can be increased, which has the effect of ensuring that the strength of the molded body is high. In other words, it has the effect of increasing the strength of the molded body in accordance with the ability to thicken the thickness of the molded body.
[0073] When the thickness reduction rate after the initial thickness is reduced by more than 5 mm is 0.070 mm / hour or more when kept in water at 49°C, the tensile strength of the molded body of one embodiment of the present invention at 49°C is preferably 52 MPa or more, more preferably 54 MPa or more, and further preferably 56 MPa or more. If the above tensile strength is 52 MPa or more, the following effects are achieved: the thickness of the molded body required to function as a downhole tool can be reduced, and the time required to achieve complete decomposition can be shortened. In other words, the following effects are achieved: the part that functions as a downhole tool can be made thinner and the decomposition time of the part can be shortened accordingly.
[0074] As described above, a molded body according to one embodiment of the present invention contains a specific cyclic ester and an inorganic filler. The cyclic ester has the effect of increasing the water absorption of the glycolic acid polymer and accelerating the decomposition of the molded body. In addition, the water absorption of the glycolic acid polymer is increased by the decomposition of the inorganic filler, and the decomposition of the molded body is accelerated. It is speculated that the molded body containing the above-mentioned specific cyclic ester and inorganic filler promotes the dissolution of the cyclic ester through the alkaline component produced by the decomposition of the inorganic filler, and the diffusion rate of water in the molded body is increased, thereby increasing the thickness reduction rate of the molded body in the late stage of decomposition. As shown in the examples, compared with a molded body containing only a cyclic ester and a molded body containing only an inorganic filler, the molded body according to one embodiment of the present invention has a high thickness reduction rate in the late stage of decomposition while maintaining tensile strength due to the synergistic effect of the specific cyclic ester and the inorganic filler.
[0075] (Method for producing molded article)
[0076] The molded article of the present embodiment can be obtained by molding the above-mentioned composition. The molding method is not limited, and examples thereof include injection molding, melt extrusion molding, solidification extrusion molding, compression molding (press molding), and centrifugal molding.
[0077] An example of the case where a molded body is manufactured by solidification extrusion molding is shown. The pellets composed of the composition are supplied to an extruder with a barrel set to be above the melting point of the composition and below 255°C (usually 200-255°C) for melt kneading. Next, the molten kneaded material is extruded from the extrusion die at the top of the extruder into the flow path of the molding die, cooled to below the crystallization temperature of the composition in the flow path of the molding die to solidify it, and extruded to the outside at a speed of 5-50mm / 10 minutes from the top of the molding die. The extrudate is pressurized and towed while applying a back pressure of 1500-8500kg in the direction of the molding die, thereby manufacturing a molded body as a solidified extrusion molding. The molded product can also be annealed by heat treatment at a temperature of 150-230°C for 3-24 hours.
[0078] An example of the case where a molded body is manufactured by injection molding is shown. The pellets composed of the composition are supplied to an injection molding machine equipped with a mold for injection molding. The temperature of the barrel is set to be above the melting point of the composition and below 255°C (usually 200-255°C), and the mold temperature is set to be above 0°C and below the melting point of the composition (usually 0-190°C). Then, injection molding is performed at an injection pressure of 1-104MPa (preferably 10-104MPa) to manufacture a molded body as an injection molded product. The molded product can also be annealed at a temperature above the crystallization temperature of the composition and below the melting point (usually 70-220°C) for 1 minute to 10 hours.
[0079] From the perspective of machining of downhole tool components, the thickness or diameter of the molded body is preferably 1 mm or more, more preferably 3 mm or more. In addition, the upper limit of the thickness or diameter of the molded body is not particularly limited, but is preferably 500 mm or less, more preferably 400 mm or less.
[0080] 〔Downhole tool components〕
[0081] A downhole tool component according to one embodiment of the present invention is a component used in underground excavation for recovering hydrocarbon resources such as oil and gas from underground, and is composed of the above-mentioned molded body. The molded body can be used as a downhole tool component as it is, or the downhole tool component can be manufactured by performing conventionally known mechanical processing (secondary processing). As an example of mechanical processing, cutting processing can be cited.
[0082] The shape and size of the downhole tool component of one embodiment of the present invention are not particularly limited, for example, the thickness or diameter is 5 to 500 mm, preferably 20 to 300 mm, and more preferably 30 to 200 mm. In addition, the shape of the downhole tool component can be various shapes such as round rods, flat plates, hollow products such as tubes, and special-shaped products. Considering that the extrusion molding and subsequent densification treatment are easy and most of them are suitable for extruded products as raw materials for machining, the shape of the downhole tool component is preferably a round rod, a hollow product or a flat plate. In order to form a core rod of a downhole tool component for oil excavation, especially an isolation plug, the shape of the downhole tool component is more preferably a round rod.
[0083] 〔Downhole tools〕
[0084] A downhole tool of one embodiment of the present invention includes a downhole tool component. In this specification, a device or its component disposed in a well for various well treatments such as well excavation, well blocking, and fracturing is referred to as a downhole tool. The shape of the downhole tool is not particularly limited, and for example, it can be made into a previously known shape. Examples of downhole tools include: fracturing plugs, bridge plugs, cement fixers, perforating guns, sealing balls, hole plugging devices, and packers.
[0085] 〔Summarize〕
[0086] The molded body of the first aspect of the present invention is formed from a composition comprising a glycolic acid polymer, a cyclic ester, and an inorganic filler, wherein the content of the cyclic ester in the composition is 10% by mass or more and 22% by mass or less, the content of the inorganic filler is 0.1% by mass or more and 15% by mass or less, and the inorganic filler is at least one inorganic filler selected from the group consisting of aluminum nitride and silicon nitride, and has a thickness or a diameter greater than 5 mm.
[0087] The molded article of aspect 2 of the present invention may be, in aspect 1 above, wherein when kept in water at 49° C., a thickness reduction rate after a thickness reduction of 5 mm or more from an initial thickness may be 0.070 mm / hour or more.
[0088] The molded product of scheme 3 of the present invention may be, in the above scheme 1 or 2, the tensile strength at 49°C may be 52 MPa or more, and the thickness reduction rate after the initial thickness is reduced by 5 mm or more when kept in water at 49°C may be 0.070 mm / hour or more.
[0089] The molded article according to aspect 4 of the present invention may be any one of aspects 1 to 3 above, wherein the cyclic ester in the composition is glycolide.
[0090] The molded article according to aspect 5 of the present invention, in any one of aspects 1 to 4, may be such that the content of the cyclic ester in the composition is 20% by mass or less.
[0091] The molded article according to aspect 6 of the present invention, in any one of aspects 1 to 5, may be such that a content of the inorganic filler in the composition is 10% by mass or less.
[0092] The molded article of aspect 7 of the present invention may be any one of aspects 1 to 6, wherein the glycolic acid polymer is a copolymer in which a linear polymer chain A composed of repeating units derived from glycolic acid and a polymer chain B different from the polymer chain A are chemically bonded.
[0093] The molded article according to aspect 8 of the present invention may be the molded article according to aspect 7 above, wherein the polymer chain B is derived from a polymer compound having a glass transition temperature of less than 45°C.
[0094] The molded article according to aspect 9 of the present invention may be such that, in aspect 7 or 8, the glycolic acid polymer is a block copolymer of the polymer chain A and the polymer chain B.
[0095] The molded article according to aspect 10 of the present invention may be, in aspect 7 above, wherein the glycolic acid polymer is a homopolymer of glycolic acid.
[0096] The molded article according to aspect 11 of the present invention may be any one of aspects 1 to 10, wherein the weight average molecular weight of the composition is 150,000 to 500,000.
[0097] A downhole tool member according to a twelfth aspect of the present invention is composed of the molded body according to any one of the above-mentioned first to eleventh aspects.
[0098] The downhole tool of solution 13 of the present invention includes the downhole tool component of solution 12 above.
[0099] The following examples are shown to further illustrate the embodiments of the present invention. Of course, it goes without saying that the following examples of the present invention are not limited to the following examples, and the details can take various forms. Moreover, the present invention is not limited to the above-mentioned embodiments, and various changes can be made within the scope shown in the claims. The embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. In addition, all the documents recorded in this specification are cited as references.
[0100] Example
[0101] Hereinafter, the composition of the glycolic acid polymer obtained by polymerization is referred to as a "polymer composition". In addition, a composition containing a glycolic acid polymer (or a polymer composition), a cyclic ester, and an inorganic filler is simply referred to as a "composition". In addition, the composition of the glycolic acid polymer used in the measurement of the SP value below is simply referred to as a "mixture".
[0102] In the following examples, % means mass % unless otherwise specified.
[0103] [Determination of SP Values of Glycolic Acid Polymers and Cyclic Esters]
[0104] The SP value was measured with reference to "SP Value Fundamentals / Application and Calculation Method" by Hideki Yamamoto (published by Information System Co., Ltd. (2005) pp. 66-67). More specifically, the SP value δ (cal / cm2) of the target compound (glycolic acid polymer or cyclic ester) was calculated according to the following formula (1): 3 ) 1 / 2 ).
[0105] δ=(ΣEcoh / ΣV) 1 / 2 ……(1)
[0106] In formula (1), ΣEcoh represents Ecoh (the cohesive energy density (cal / cm 3 ));ΣV represents V(the molar molecular volume (cm 3 )).
[0107] The results of the measurement of the SP value, the difference between the SP value of the cyclic ester and the SP value of the glycolic acid polymer, and the glass transition temperature of the mixture are shown in Table 1. The SP value of the glycolic acid polymer is 26.8. In addition, when the mixture contains two kinds of cyclic esters, the absolute value of the difference between the SP value of each cyclic ester and the SP value of the glycolic acid polymer is larger than that of the difference between the SP values of the cyclic esters.
[0108] [Table 1]
[0109]
[0110] [Evaluation of composition and molded article]
[0111] The compositions and molded products obtained in Examples and Comparative Examples were evaluated as follows.
[0112] (Measurement of Weight Average Molecular Weight of Molded Article)
[0113] About 10 mg of the sample was dissolved in 0.5 mL of DMSO at 150°C and cooled to room temperature. The cooled solution was fixed to 10 mL with hexafluoroisopropanol (HFIP) and the weight average molecular weight of the composition was measured using a GPC device. Polymethyl methacrylate (PMMA) was used as a standard substance. The measurement conditions are as follows.
[0114] Apparatus: shodexGPC-104 (detector: RI, chromatographic columns: two HFIP-606M).
[0115] Solvent: HFIP containing 5 mM CF3COONa.
[0116] (Determination of glycolide content in molded article)
[0117] To about 100 mg of the sample, DMSO containing p-chlorobenzophenone (0.4 mg / 2 mL) was added and dissolved by heating at 150°C for about 10 minutes. After cooling to room temperature, the solution was filtered. The obtained filtrate was measured by gas chromatography (GC). The measurement conditions are as follows.
[0118] Device: Shimadzu GC-2010.
[0119] Column: RESTEK Rxi-5ms.
[0120] Column temperature: maintain at 150°C for 5 minutes → (increase temperature at 20°C / min) → maintain at 270°C for 3 minutes.
[0121] Injection temperature: 180℃.
[0122] (Measurement of thickness reduction rate of molded body)
[0123] For the molded body, the required number of cubic test pieces with a side of 13 mm or 40 mm were prepared. Next, the test piece was placed in a 1L autoclave at a temperature of 49°C. Then, the autoclave was filled with water (deionized water) and an immersion test was performed. The immersed test piece was taken out at a specified time interval and cut to expose the cross section. Then, after being placed in a drying room overnight to dry, the thickness of the core (hard part) of the test piece was measured. The reduced thickness was measured based on the difference from the thickness before immersion (initial thickness, specifically 13 mm or 40 mm). Based on the measured value of the reduced thickness of the test piece measured according to different immersion times, the time change of the reduced thickness of the test piece was calculated. Here, the period of thickness reduction of 0 to 5 mm is defined as the initial decomposition period, and the period of thickness reduction of more than 5 mm is defined as the late decomposition period. Based on the time change of the reduced thickness of the test piece within the range of the initial decomposition period or the late decomposition period, the thickness reduction rate (unit: mm / h) of the test piece with a thickness of 13 mm or 40 mm is calculated.
[0124] (Measurement of tensile strength of molded article)
[0125] The molded product of the present invention having an effective thickness of 5 mm or more can be said to have a sufficient tensile strength for practical use as long as the tensile strength measured by the specified test piece is 52 MPa or more. The tensile strength of the test piece can be measured in accordance with ISO527-1. For a test piece of the shape specified in ISO527-1 (test piece No. 5), a tensile test is performed at 49°C (temperature 49°C ± 1°C) at a speed of 20 mm / min, and the maximum point stress shown during the period until the test piece breaks is calculated as the tensile strength of the test piece (average value of n = 5. Unit: MPa).
[0126] [Example 1]
[0127] Into a polymerization container, 0.03 parts by mass of tin dichloride as a catalyst, 1 part by mass of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as a heat stabilizer, and 2 parts by mass of polyethylene glycol (PEG, Mw 7500) as a polymerization initiator were charged with respect to 100 parts by mass of glycolide. The charged contents were kept under heating conditions of 140° C. for 6 hours to obtain a polymer composition 1. Polymer composition 1 did not contain glycolide.
[0128] Glycolide (GL) as a cyclic ester, aluminum nitride (AlN) as an inorganic filler, pyromellitic dianhydride (PMDA) as a decomposition accelerator, and a mixture of distearyl acid phosphate and monostearyl acid phosphate ("ADK STAB AX-71" manufactured by ADEKA Corporation) as a heat stabilizer were added to polymer composition 1 to obtain a composition. The contents of the cyclic ester, inorganic filler, and decomposition accelerator contained in the composition are shown in Table 2.
[0129] The composition was supplied to the feed section of a twin-screw extruder kneading machine ("2D25S" manufactured by Toyo Seiki Co., Ltd.) with the screw temperature set to 190 to 240°C for melt kneading and extrusion molding to obtain pellets of the composition. Then, the pellets of the composition were supplied to the feed section of an injection molding machine ("EC-100N" manufactured by Toshiba Machine) with the barrel temperature set to 190 to 240°C for injection molding to obtain a molded body. The mold temperature during injection molding was set to 80 to 100°C.
[0130] [Examples 2 and 3]
[0131] A composition and a molded body were obtained in the same manner as in Example 1 except that the blending amounts of the cyclic ester and the inorganic filler were changed. Table 2 shows the contents of the cyclic ester and the inorganic filler in Examples 2 and 3.
[0132] [Example 4]
[0133] A composition and a molded body were obtained in the same manner as in Example 1 except that the amounts of the cyclic ester and the inorganic filler were changed and no decomposition accelerator was added. The contents of the cyclic ester, the inorganic filler and the decomposition accelerator in Example 4 are shown in Table 2.
[0134] [Example 5]
[0135] 0.003 parts by mass of tin dichloride as a catalyst and 0.3 parts by mass of 1-dodecanol as a polymerization initiator were charged into a polymerization container relative to 100 parts by mass of glycolide. The charged contents were kept at 170° C. for 2 hours to obtain a polymer composition 2. Polymer composition 2 did not contain glycolide.
[0136] Glycolide (GL) as a cyclic ester, aluminum nitride (AlN) as an inorganic filler, pyromellitic dianhydride (PMDA) as a decomposition accelerator, and a mixture of distearyl acid phosphate and monostearyl acid phosphate ("ADK STAB AX-71" manufactured by ADEKA Corporation) as a heat stabilizer were added to polymer composition 2 to obtain a composition. The contents of the cyclic ester, inorganic filler, and decomposition accelerator contained in the composition are shown in Table 2.
[0137] [Examples 6 to 8]
[0138] A composition and a molded body were obtained in the same manner as in Example 5 except that the amounts of the cyclic ester, the inorganic filler and the decomposition accelerator were changed. Table 2 shows the contents of the cyclic ester, the inorganic filler and the decomposition accelerator in Examples 6 to 8.
[0139] [Example 9]
[0140] A composition and a molded body were obtained in the same manner as in Example 5 except that the amount of the cyclic ester added was changed and no decomposition accelerator was added. The contents of the cyclic ester and the inorganic filler in Example 9 are shown in Table 2.
[0141] [Examples 10 and 11]
[0142] A composition and a molded product were obtained in the same manner as in Example 9 except that the amounts of the cyclic ester and the inorganic filler were changed. Table 2 shows the contents of the cyclic ester and the inorganic filler in Examples 10 and 11.
[0143] [Example 12]
[0144] A composition and a molded body were obtained in the same manner as in Example 9 except that the amount of the cyclic ester was changed and silicon nitride (SiN) was used as the inorganic filler instead of aluminum nitride. The contents of the cyclic ester and the inorganic filler in Example 12 are shown in Table 2.
[0145] [Example 13]
[0146] A composition and a molded product were obtained in the same manner as in Example 12 except that the amount of the inorganic filler was changed. Table 2 shows the contents of the cyclic ester and the inorganic filler in Example 13.
[0147] [Comparative Examples 1 and 2]
[0148] A composition and a molded body were obtained in the same manner as in Example 1 except that the amounts of the cyclic ester and the decomposition accelerator were changed and no inorganic filler was added. Table 3 shows the contents of the cyclic ester and the decomposition accelerator in Comparative Examples 1 and 2.
[0149] [Comparative Examples 3 and 4]
[0150] A composition and a molded body were obtained in the same manner as in Comparative Example 1 except that the amount of the cyclic ester added was changed and no decomposition accelerator was added. Table 3 shows the contents of the cyclic ester and the decomposition accelerator in Comparative Examples 3 and 4.
[0151] [Comparative Examples 5 and 6]
[0152] A composition and a molded article were obtained in the same manner as in Comparative Example 3 except that the polymer composition 1 was changed to the polymer composition 2 and the amount of the cyclic ester added was changed. Table 3 shows the contents of the cyclic ester and the decomposition accelerator in Comparative Examples 5 and 6.
[0153] [Comparative Example 7]
[0154] A composition and a molded body were obtained in the same procedure as in Comparative Examples 5 and 6 except that a decomposition accelerator was added and a cyclic ester was not added.
[0155] [Comparative Example 8]
[0156] A composition and a molded body were obtained in the same manner as in Comparative Example 7 except that aluminum nitride was used as the inorganic filler.
[0157] [Comparative Example 9]
[0158] A composition and a molded body were obtained in the same procedure as in Comparative Examples 5 and 6 except that the amount of the cyclic ester was changed and alumina (Al2O3) was used as the inorganic filler. The types and contents of the cyclic ester and the inorganic filler in Comparative Example 9 are shown in Table 3.
[0159] [Comparative Example 10]
[0160] A composition and a molded body were obtained in the same manner as in Comparative Example 9 except that calcium oxide (CaO) was used as the inorganic filler instead of aluminum oxide. Table 3 shows the types and contents of the cyclic ester and the inorganic filler in Comparative Example 10.
[0161] [Comparative Example 11]
[0162] A composition and a molded product were obtained in the same manner as in Example 1 except that the amounts of the cyclic ester and the inorganic filler were changed. Table 3 shows the contents of the cyclic ester and the inorganic filler in Example 11.
[0163] [Comparative Example 12]
[0164] A composition and a molded body were obtained in the same manner as in Comparative Example 11 except that the amounts of the cyclic ester and the inorganic filler were changed and silicon nitride (SiN) was used instead of aluminum nitride as the inorganic filler. The contents of the cyclic ester, inorganic filler and decomposition accelerator in Comparative Example 12 are shown in Table 3.
[0165] [Comparative Example 13]
[0166] A composition and a molded body were obtained in the same manner as in Comparative Example 11 except that the amount of cyclic ester added was changed and boron nitride (BN) was used instead of aluminum nitride as the inorganic filler. The contents of cyclic ester, inorganic filler and decomposition accelerator in Comparative Example 13 are shown in Table 3.
[0167] [Comparative Example 14]
[0168] A composition and a molded body were obtained by the same procedure as in Example 5 except that calcium carbonate (CaCo3) was used instead of aluminum nitride as an inorganic filler and the amounts of the cyclic ester, inorganic filler and decomposition accelerator were changed. The contents of the cyclic ester, inorganic filler and decomposition accelerator of Comparative Example 14 are shown in Table 3.
[0169] [Comparative Example 15]
[0170] A composition and a molded body were obtained in the same manner as in Comparative Example 14 except that the blending amounts of the cyclic ester and the inorganic filler were changed. Table 3 shows the contents of the cyclic ester, the inorganic filler, and the decomposition accelerator in Comparative Example 15.
[0171] [Comparative Example 16]
[0172] A composition and a molded body were obtained in the same manner as in Example 5 except that the amounts of the cyclic ester and inorganic filler were changed and carbon fiber (CF) was used instead of aluminum nitride as the inorganic filler. The contents of the cyclic ester, inorganic filler and decomposition accelerator of Comparative Example 16 are shown in Table 3.
[0173] [Comparative Examples 17 and 18]
[0174] A composition and a molded body were obtained in the same manner as in Example 5 except that the amount of the cyclic ester was changed and no inorganic filler was added. Table 3 shows the contents of the cyclic ester and the decomposition accelerator in Comparative Examples 17 and 18.
[0175] [Comparative Example 19]
[0176] A composition and a molded body were obtained in the same manner as in Example 5 except that the amount of the cyclic ester was changed and the inorganic filler and the decomposition accelerator were not added. Table 3 shows the contents of the cyclic ester and the decomposition accelerator in Comparative Example 19.
[0177] The inorganic fillers used in the examples and comparative examples were all in the form of particles.
[0178] [Table 2]
[0179]
[0180]
[0181] [Table 3]
[0182]
[0183]
[0184] It can be seen that in Comparative Examples 1 to 7 and 17 to 19 where no inorganic filler is added, only one of the maximum point stress of 52 MPa or more and the thickness reduction rate of 0.07 mm / hour or more in the late stage of decomposition can be satisfied. In contrast, in Examples 1 to 14 where inorganic fillers are added, both characteristics can be taken into account. On the other hand, as shown in Comparative Example 8, even if an inorganic filler is added in a state where no cyclic ester is added, the decomposition acceleration effect is not observed, so it can be seen that the cyclic ester and the inorganic filler work synergistically to enhance the decomposition acceleration effect. In addition, as shown in Comparative Examples 9, 10 and Comparative Examples 14 to 16, it can be seen that if a non-nitride inorganic filler is added, injection molding cannot be performed due to thermal decomposition, or only one of the maximum point stress of 52 MPa or more and the thickness reduction rate of 0.07 mm / hour or more in the late stage of decomposition can be satisfied. In addition, as shown in Comparative Examples 11 to 13, it can be seen that if the content of the cyclic ester is set outside the range of 10 mass % or more and 22 mass % or less, the maximum point stress of 52 MPa or more cannot be satisfied.
[0185] Industrial Applicability
[0186] The molded article of the present invention has a high decomposition rate and can be used, for example, as a downhole tool for well excavation.
Claims
1. A molded body, the molded body being formed from a composition comprising a glycolic acid polymer, a cyclic ester and an inorganic filler, The content of the cyclic ester in the composition is 10% by mass or more and 22% by mass or less, and the content of the inorganic filler is 0.1% by mass or more and 15% by mass or less, The inorganic filler is at least one inorganic filler selected from the group consisting of aluminum nitride and silicon nitride, The thickness or diameter of the shaped body is greater than 5 mm.
2. The molded article according to claim 1, in, When kept in water at 49° C., the rate of thickness reduction after the initial thickness is reduced by 5 mm or more is 0.070 mm / hour or more.
3. The molded article according to claim 1, in, The tensile strength at 49° C. is 52 MPa or more, and when kept in water at 49° C., the rate of thickness reduction after the initial thickness is reduced by 5 mm or more is 0.070 mm / hour or more.
4. The molded article according to claim 1, in, The cyclic ester in the composition is glycolide.
5. The molded article according to claim 1, in, The content of the cyclic ester in the composition is 20% by mass or less.
6. The molded article according to claim 5, in, The content of the inorganic filler in the composition is 10% by mass or less.
7. The molded article according to claim 1, in, The glycolic acid polymer is a copolymer in which a linear polymer chain A composed of repeating units derived from glycolic acid and a polymer chain B different from the polymer chain A are chemically bonded.
8. The molded article according to claim 7, in, The polymer chain B is derived from a polymer compound having a glass transition temperature lower than 45°C.
9. The molded article according to claim 7, in, The glycolic acid polymer is a block copolymer of the polymer chain A and the polymer chain B.
10. The molded article according to claim 1, in, The glycolic acid polymer is a homopolymer of glycolic acid.
11. The molded article according to claim 1, in, The weight average molecular weight of the composition is 150,000 or more and 500,000 or less.
12. A downhole tool component, the downhole tool component being composed of the molded body according to any one of claims 1 to 11.
13. A downhole tool comprising the downhole tool member according to claim 12.
